(untitled) (Conferencea, 2023)
Regional policy is the state regulation of the socio-economic development of the first and second regions. Its main task is to bring the level of socio-economic development of all regions of the country as close as possible to each other due to the rational use of existing opportunities, to minimize regional differences in the distribution of material goods between different strata of the population, to reduce the management tasks of the government, and to reduce the administrative tasks of local authorities and self-government bodies. should be focused on increasing the authority.